Uridine‐responsive epileptic encephalopathy due to inherited variants in CAD: A Tale of Two Siblings. Issue 3 (26th January 2021) - McGraw, Christopher M.; Mahida, Sonal; Jayakar, Parul; Koh, Hyun Yong; Taylor, Alan; Resnick, Trevor; Rodan, Lance; Schwartz, Marc A.; Ejaz, Ayesha; Sankaran, Vijay G.; Berry, Gerard; Poduri, Annapurna
Abstract: We report two siblings with intractable epilepsy, developmental regression, and progressive cerebellar atrophy due to biallelic variants in the gene CAD . For the affected girl, uridine started at age 5 resulted in dramatic improvements in seizure control and development, cessation of cerebellar atrophy, and resolution of hematological abnormalities. Her older brother had a more severe course and only modest response to uridine started at 14 years old. Treatment of this progressive condition via uridine supplementation provides an example of precision diagnosis and treatment using clear outcome measures and biomarkers to monitor efficacy.